Partisipasi Generasi Milenial dalam Kancah Politik Nasional 2019 - Candranegara, I Made Wimas; Mahardhika, I Putu Eka; Mirta, I Wayan (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
Millennials generations are valuable assets owned by the Indonesian people. The number of generations reaching approximately 35% now makes every politician interested in getting feedback from this generation. The millennial generation currently has a very broad momentum, one of which is in terms of political participation in Indonesia. The activity of this millennial generation is able to change the direction and pace of Indonesian politics towards being identical to this generation's habit. His appearance to be active in political participation today has changed Indonesia's political paradigm a lot. Young figures with very different communication styles compared to their predecessor's style make this millennial generation has its own distinctive characteristics and colors in the Indonesian public sphere. Besides that Indonesia, which is currently entering the gate of industrial revolution 4.0, must certainly adapt to the pace of the era and change the paradigm of a very fast generation especially in 2030 Indonesia will experience a demographic bonus, so that readiness and maturity in the political world for the millennial generation is very important to prepare since early.